2018
DOI: 10.1007/s00586-018-5838-z
|View full text |Cite|
|
Sign up to set email alerts
|

Intervertebral disc penetration by antibiotics used prophylactically in spinal surgery: implications for the current standards and treatment of disc infections

Abstract: Purpose The presence of Propionibacterium acnes in a substantial component of resected disc specimens obtained from patients undergoing discectomy or microdiscectomy has led to the suggestion that this prominent human skin and oral commensal may exacerbate the pathology of degenerative disc disease. This hypothesis, therefore, raises the exciting possibility that antibiotics could play an important role in treating this debilitating condition. To date, however, little information about antibiotic penetration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Colonization of LIVD by C . acnes in patients with LDD supports the bacterial hypothesis of LBP [ 4 , 8 , 29 , 45 47 ]. The determination of a molecular profile for these patients will not only contribute to a better understanding of the pathophysiological basis of LBP associated with LDD [ 41 43 ], but it will also positively interfere in the clinical management of this common condition, rationalizing its treatment and optimizing its costs.…”
Section: Hypotheses and Objectivessupporting
confidence: 68%
See 1 more Smart Citation
“…Colonization of LIVD by C . acnes in patients with LDD supports the bacterial hypothesis of LBP [ 4 , 8 , 29 , 45 47 ]. The determination of a molecular profile for these patients will not only contribute to a better understanding of the pathophysiological basis of LBP associated with LDD [ 41 43 ], but it will also positively interfere in the clinical management of this common condition, rationalizing its treatment and optimizing its costs.…”
Section: Hypotheses and Objectivessupporting
confidence: 68%
“…LBP is a common complaint in the general population, and its incidence is about five times higher in patients with LDD and Modic endplate changes [1,2]. The link between these findings and the isolation of low virulence pathogens in LIVD has already been described in several studies, generating a lot of interest in the topic and promoting the bacterial hypothesis of LDD [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Colonization of LIVD by C. acnes in patients with LDD supports the bacterial hypothesis of LBP (4,8,29,(45)(46)(47). The determination of a molecular profile for these patients will not only contribute to a better understanding of the pathophysiological (41)(42)(43), but it will also positively interfere in the clinical management of this common condition, rationalizing its treatment and optimizing its costs.…”
Section: Justificationsmentioning
confidence: 62%
“…(1,2) The link between these findings and the isolation of low virulence pathogens in LIVD has already been described in several studies, generating a lot of interest in the topic and promoting the bacterial hypothesis of LDD. (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14) Albert et al reported 46% of positive cultures for anaerobes in 61 patients undergoing lumbar discectomy, of which 80% had Modic type 1 changes. (15) Other studies corroborate these findings, with high identification rates for Cutibacterium acnes, an anaerobic and aerotolerant pathogen that is bacillus-shaped, stained by the Gram method, pleomorphic, non-spore-forming, and a biofilm producer.…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Intravia et al, cefazolin antimicrobial activity against several strains of bacteria was compared with the antimicrobial activity of PRP with and without leukocytes, but the antibiotic was a separate experimental arm in the study and not examined directly in combination with the PRP as an injectate component [25]. Since disc penetration of certain prophylactic antibiotics can be poor following intravenous administration [26], intradiscal administration of antibiotics may be required for efficacy during this and similar procedures in the clinic.…”
mentioning
confidence: 99%